Zigzag multirod laser beam merging approach for brighttem00-mode solar laser emission from a megawatt solar furnace - Costa, Hugo (2022)
An alternative multirod solar laser end-side-pumping concept, based on the megawatt solar furnace in France, is proposed to significantly improve the TEM00-mode solar laser output power level and its beam brightness through a novel zigzag beam merging technique. A solar flux homogenizer was used to deliver nearly the same pump power to multiple core-doped Nd:YAG laser rods within a water-cooled pump cavity through a fused silica window. Compared to the previous multibeam solar laser station concepts for the same solar furnace, the present approach can allow the production of high-power TEM00-mode solar laser beams with high beam brightness. An average of 1.06 W TEM00-mode laser power was numerically extracted from each of 1657 rods, resulting in a total of 1.8 kW. More importantly, by mounting 399 rods at a 30◦ angle of inclination and employing the beam merging technique, a maximum of 5.2 kW total TEM00-mode laser power was numerically extracted from 37 laser beams, averaging 141 W from each merged beam. The highest solar laser beam brightness figure of merit achieved was 148 W, corresponding to an improvement of 23 times in relation to the previous experimental record.